Implementasi Prinsip Halal Dalam Operasional Umkm Kuliner: Studi Kasus Pecel Ulek Mbah Queen - Dini Vientiany; Armita Isnaini Munthe; Fitri Ramadani; Sindy Aulia Sari (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study aims to analyze the implementation of halal principles in the operational activities of the culinary MSME Pecel Ulek Mbah Queen and to identify factors influencing its readiness for halal certification. Using a qualitative approach with a case study design, the research employed observation, in-depth interviews, and documentation to examine the use of raw materials, production processes, hygiene practices, and operational management. The findings indicate that the business has applied basic halal principles through careful ingredient selection and relatively clean production practices; however, it lacks formal documentation and systematic identification of halal-critical points as required by the Halal Assurance System. Furthermore, the owner and employees possess limited technical understanding of halal procedures, and supplier verification has not been conducted systematically. The study concludes that Pecel Ulek Mbah Queen has strong potential to achieve halal certification, but improvements are needed in documentation, halal training, workflow structuring, and technical assistance to enable a more systematic and compliant implementation of halal standards.